H7N6 highly pathogenic avian influenza in Mozambique, 2023 - Iolanda Vieira Anahory Monjane; Hernâni Djedje; Esmeralda Tamele; Virgínia Nhabomba; Almiro Rogério Tivane; Zacarias Elias Massicame; Dercília Mudanisse Arone; Ambra Pastori; Alessio Bortolami; Isabella Monne; Timothy Woma; Charles E. Lamien; et al. (Emerging Microbes and Infections, 2024)
ABSTRACTOn 13 October 2023, the National Directorate for Livestock Development in Mozambique was notified of a suspected outbreak of avian influenza in commercial layers. Samples were screened by real-time and conventional RT–PCR and were positive for both H7 and N6. Full genome sequences were obtained for three representative samples. Sequence analysis of the H7 cleavage site confirmed that the viruses were highly pathogenic (i.e. 333- PEPPKGPRFRR/GLF-346). In addition, the H7 and N6 sequences were highly similar (from 99.4-99.5% and 99.6-99.7% for the HA gene and the NA gene, respectively) to the sequences of a H7N6 virus identified in the Republic of South Africa in May 2023 indicating a similar origin of the viruses. The identification of H7N6 HPAIV in Mozambique has important implications for disease management and food security in the region.